Enhancing the Enthusiasm and Educational Achievements in Sociology Pertaining to Social Issues Arising from Social Grouping among Class XI-7 Students during the Odd Semester of the Academic Year 2022/2023 - Sri Lestari (Medan Resource Center, 2023)
The main aim of this classroom action research is divided into three parts: 1) Executing the Differentiated approach of Problem Based Learning to enhance the interest in studying Sociology pertaining to Social Issues arising from Social Grouping among Class XI-7 students, Odd Semester of the Academic Year 2022/2023. 2) Utilizing the Differentiated method of Problem Based Learning to elevate the academic achievements in Sociology concerning Social Issues resulting from Social Grouping among Class XI-7 students, Odd Semester of the Academic Year 2022/2023. 3) Applying the Differentiated model of Problem Based Learning to amplify both the enthusiasm and academic achievements in Sociology regarding Social Issues caused by Social Grouping among Class XI-7 students, Odd Semester of the Academic Year 2022/2023. The research subjects encompass the students of Class XI-7 at Batik 1 Surakarta High School during the academic year 2022/2023, encompassing a total of 38 students, comprising 18 males and 20 females. The research methodology involves three data collection techniques: (i) Documenting to compile data on initial interest and academic outcomes; (ii) Observing to monitor interest in learning throughout cycle 1 and cycle 2; (iii) Employing written tests to gauge academic outcomes in cycle 1 and cycle 2. Data is collected through a variety of tools, including documents, observation sheets, and written test items. Validation of interest in learning is conducted through the observations of an external observer, while validation of academic outcomes is achieved by developing a written test framework. The employed data analysis technique entails a comparative descriptive analysis, followed by a phase of introspection. The findings of this study reveal that: 1) The implementation of the Differentiated approach of Problem Based Learning effectively boosts interest in studying Sociology to 58.77%. 2) The application of the identical teaching approach similarly contributes to enhancing academic achievements in Sociology to 28.06%. 3) The fusion of applying the teaching model along with utilizing the Differentiated Problem Based Learning strategy leads to a rise in both enthusiasm and academic achievements in Sociology to 58.77%. All these outcomes serve to depict the efficiency of the intervention executed in this research.